Combined dietary effects of probiotics, yeast, and digestive enzymes on growth performance and meat quality in grass carp (Ctenopharyngodon idella) (Zoo Botanica, 2025)
This study investigated the effects of probiotics, yeast, and digestive enzymes as feed additive on the growth and meat quality of Grass carp. A total of 90 Fingerlings divided into three groups i.e., control (C), 2g/kg supplement (T1), and 4g/kg supplement (T2) were reared for three months in glass aquaria. The growth performance viz., weight gain, standard length, fork length and total length was measured on fortnightly basis. Proximate composition analysis was performed at the end of the experiment to evaluate meat quality of Grass carp. The group receiving 4g/kg of the supplementation (T2) shows higher values for all growth parameters, followed by T1 and C group respectively. The proximate analysis revealed significantly better meat quality, characterized by higher crude protein (64.80±1.63) with lower crude fat, moisture and ash content (16.60±0.65, 73.50±0.61, 9.13±0.41) in T2 as compared to T1 and C group. The overall outcome revealed that the supplementary diet with addition of probiotics, yeast, and digestive enzymes is a good source of nutrients and fiber for Grass carp that helps to improve the growth and meat quality of fish species.
Keywords: Grass carp; probiotics; growth performance; meat quality